Overexpression of the Thyroid Hormone-Responsive (THRSP) Gene in the Striatum Leads to the Development of Inattentive-like Phenotype in Mice. (15th October 2018) - Custodio, Raly James Perez; Botanas, Chrislean Jun; de la Peña, June Bryan; dela Peña, Irene Joy; Kim, Mikyung; Sayson, Leandro Val; Abiero, Arvie; Ryoo, Zae Young; Kim, Bung-Nyun; Kim, Hee Jin; Cheong, Jae Hoon
Highlights: Thyroid-hormone responsive (THRSP) overexpressing (OE) mice exhibits inattention, but not hyperactivity and impulsivity. THRSP OE mice have elevated striatal dopamine-related gene (DAT, TH, and dopamine D1 and D2 receptors) expression levels. Methylphenidate improves attention in THRSP OE mice. Methylphenidate normalizes the expression levels of dopaminergic-related genes in the striatum of THRSP OE mice. THRSP OE mice can be a potential mouse model for ADHD-inattentive type. Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder that affects 8–12% of children globally. Factor analyses have divided ADHD symptoms into two domains: inattention and a combination of hyperactivity and impulsivity. The identification of domain-specific genetic risk variants may help uncover potential genetic mechanisms underlying ADHD. We have previously identified that thyroid hormone-responsive (THRSP) gene expression is upregulated in spontaneously hypertensive rats (SHR/NCrl) and Wistar-Kyoto (WKY/NCrl) rats which exhibited inattention behavior. Thus, we established a line of THRSP overexpressing (OE) mice and assessed their behavior through an array of behavioral tests. The gene and protein overexpression of THRSP in the striatum (STR) was confirmed by quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting. The THRSP OE mice exhibited inattention in the novel-object recognition and Y-maze test, but not hyperactivity in the open-field test and impulsivity in the cliff-avoidance and delay-discounting task. We have also found that expression of dopamine-related genes (dopamine transporter, tyrosine hydroxylase, and dopamine D1 and D2 receptors) in the STR increased. Treatment with methylphenidate (5 mg/kg), the most commonly used medication for ADHD, improved attention and normalized expression levels of dopamine-related genes in THRSP OE mice. Our findings suggest that THRSP plays a role in the inattention phenotype of ADHD and that the THRSP OE mice may be used as an animal model to elucidate the genetic mechanisms of the disorder.